From flag to flag - Ripley, Eliza, 1832-1912 (Salt Lake City, UT : Project Gutenberg, 2023)
"From Flag to Flag" by Eliza McHatton-Ripley is a historical account written in the late 19th century. The narrative chronicles the experiences and adventures of a woman in the South during the American Civil War, as well as her journeys through Mexico and Cuba. The author reflects on the sociopolitical turmoil of the era, offering a vivid portrayal of life in a plantation home, the unfolding war, and the impact on families and communities, particularly from a woman's perspective. At the start of the book, the author introduces her life on a Louisiana plantation named Arlington, reminiscing about the beauty and peace of her early married life. As tensions rise in the nation leading to the Civil War, the community is seen organizing efforts to support the Confederate cause, which ultimately transforms their idyllic lives into a struggle for survival amid conflict. The opening sets the stage for a broader exploration of personal and historical upheaval, painting a picture of the changing tides of life during a turbulent time in American history. (This is an automatically generated summary.)
Release date is 2023-03-14
Emmanuel Ackerman and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Mexico -- Description and travel; Louisiana -- History -- Civil War, 1861-1865; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate; Cuba -- Description and travel; Ripley, Eliza, 1832-1912